THE RELIABILITY OF GLASGOW COMA SCALE (GCS) EXAMINATION OF STROKE PATIENTS IN SARDJITO HOSPITAL - , MUHAMMAD SALLEHUDDIN AMIRUDIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: The mini-mental state exam (MMSE) has been used to evaluate the cognitive function of patients. However, many things can affect a patient's MMSE score such as their age, education level and current neurological disorder. It is therefore important to know whether the MMSE scores of stroke patients in stroke unit is different from the general population. Objective: To determine the reliability of Glasgow Coma Scale examination of stroke patients in RSUP Dr. Sardjito, Yogyakarta. Method: The study done is a descriptive and prospective study. The data will be obtained prospectively from the stroke patients diagnosed in Unit Stroke RSUP Dr. Sardjito, Yogyakarta. Result: The Cohenâs Kappa analysis show reliability of inter-reter agreement 0.944 (p<0,001) and good internal consistency of 0.81. Conclusion: The Glasgow Coma Scale (GCS) examination is a reliable tool to assess the level of consciousness in stroke patients of RSUP Dr. Sardjito.